Foreign policy positioning issue of small States (on the example of the Republic of Belarus relations with the Russian Federation and People’s Republic of China) - Salmygina, Е.Д. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
Small states are very weak in the political area. That is why there is a need for them to try to choose the various foreign policy strategies to defend themselves. Belarus is a small state that needs to survive in our rapidly developing and politically unstable world. Having emerged as a newly independent state as the result of the collapse of the USSR, Belarus faced a difficult choice in the decision where it was going to move further and on whom it could rely. In particular, in recent years, Belarus needs to make a subtle strategic calculation as to how to manage its relations with two important partners: Russia and China. This article considers the theory of small states’ foreign policy strategies in detail. It analyzes the choice of Belarus’s foreign policy strategies towards China and Russia. It shows that Belarus combines some characteristics from the classic small states’ foreign policy strategies, and it does not fully follow any of them.